Getting it all done - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2021)
"Stop juggling; start managing everything you need to do at home and at work. It used to be simple: Stay late, turn in flawless work, catch up on sleep later. You needed that mind-set to get where you are, but that's not going to cut it anymore. You need to make different choices to succeed at work, as a parent, and as a family member. Getting Things Done at Home and Work can't teach you how to be in two places at once, but it provides you with expert advice as you manage the challenge of succeeding at work while making sure your family is housed, fed, healthy, safe, and educated. You'll learn to: set up schedules and routines that work, spend your time and energy on the most valuable activities, set reasonable expectations and limits in the always-on culture, keep exercising your management skills once you've left the office, move on with resilience when you occasionally drop the ball. embody the work and life values you believe in for your children"--
Section 1. Kanban in the kitchen -- bring your work skills home: To have a happier home life, treat it a little more like work -- plan and schedule, play to their strengths, and put people first / by Whitney Johnson -- The agile family meeting -- transform your family by asking three questions / by Bruce Feiler -- Sync up your family calendars -- with fewer bad surprises, everyone is happier / by Elizabeth Grace Saunders -- Negotiating with your kids -- you can't fire them and they can't quit. You'd better find a win-win / by Mary C. Kern and Terri R. Kurtzberg -- Assemble your "parenting posse" -- networking helps at home, too / by Alison Beard -- Section 2. Say no to doing everything: -- put your real priorities first: Does your schedule reflect your values? -- learn to translate your priorities into action / by Elizabeth Grace Saunders -- Let go of the idea of balance -- look for four-way wins: an HBR IdeaCast Interview with Stewart D. Friedman and Alyssa F. Westring -- Put your parenting energy in the right places -- when was the last time you checked in on your kids' priorities? / by Amy Jen Su -- "Delegating with joy" -- to get the help you need, put a task and an ask in a higher context: a Women at Work Interview with Tiffany Dufu -- Too much to do? Here's how to ask for help -- figure out what you need, just ask for it, and accept what is offered / by Heidi Grant -- How to say no to taking on more -- practice saying it out loud / by Rebecca Knight -- Section 3. Getting it all (mostly) done -- productivity tips and hacks you need: How to work from home when you have kids -- it takes more than a home office / by Daisy Wademan Dowling -- You can make family meals happen -- consider family breakfast / by Daisy Wademan Dowling -- Fifteen ideas for getting more done / by fifteen HBR readers, authors, and editors -- How working parents can manage the demands of school-age kids -- strategies to handle the chaos / by Daisy Wademan Dowling -- Stop feeling guilty ab
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 15, 2021).
WorldCat record variable field(s) change: 050
Keywords: Work and family; Parenting; Work-life balance; Parenting; Work and family; Work-life balance; elektronické knihy; electronic books